Depression and the Link with Cardiovascular Disease - Dhar, Arup K.; Barton, David A. (Frontiers in Psychiatry, 2016)
This review provides an outline of the association between major depressive disorder (MDD) and coronary heart disease (CHD). Much is known about the two individual clinical conditions; however it is not until recently, that biological mechanisms have been uncovered that link both MDD and CHD. The activation of stress pathways have been implicated as a neurochemical mechanism that links MDD and CHD. Depression is known to be associated with poorer outcomes of CHD. Psychological factors such as major depression and stress are now known as risk factors for developing CHD which is as important and is independent of classic risk factors such as hypertension, diabetes mellitus and cigarette smoking. Both conditions have great socioeconomic importance given that depression and CHD are likely to be two of the three leading causes of global burden of disease. Better understanding of the common causal pathways will help us delineate more appropriate treatments.